The Concept of Intersectionality in Patricia Collins’s Black Feminism - Santibañez Guerrero, Daniel (Resonancias. Revista de Filosofía, 2018)
Within the main currents of political feminism developed in the late twentieth century, black feminism is surely one of the most comprehensive philosophical attempts to examine the theoretical basis of sexism and discrimination against women. Within these approaches, the account of Patricia Collins will address the historical and cultural nexus that the concepts “sex”, “gender” and “race” would present from the perspective of "intersectionality ", with black women being understood as one of the ultimate forms (if not the greatest) of exclusion and submission of the human being.